Nomenclature and taxonomy of the partial infrageneric classification systems proposed for Kalanchoe (Crassulaceae subfam. Kalanchooideae) by Boiteau and Boiteau & Mannoni in the mid-20th century - Smith, Gideon F.; Shtein, Ronen (Phytotaxa, 2022)
The partial infrageneric classification systems proposed for Kalanchoe (Crassulaceae subfam. Kalanchooideae) by Boiteau and Boiteau & Mannoni during the mid-20th century are analysed. The pertinent work of Boiteau published in 1947, as subsequently elaborated on by Boiteau & Mannoni in the late-1940s, is assessed to clarify the use of infrageneric ranks by these authors. From this analysis it is evident that, with the exception of two new combinations published by Boiteau in 1947 at the rank of section and two at the rank of subsection, and one unranked infrageneric name published by Boiteau & Mannoni in 1949, none of the other infrageneric designations that they proposed was validly published.